Endodontic therapy and restorative rehabilitation versus extraction and implant replacement - Abdullah A Al Shareef; Abdelhamied Y Saad (Wolters Kluwer Medknow Publications, 2013)
This investigation presents a chart that can assist clinicians, in general and endodontists, in particular, in making the right decision when they are deciding, which rout to take; endodontic treatment to save the natural tooth or extraction and osseointegrated implant. Systematic review of the literature was used to investigate success rates of both endodontic therapy and extraction of the tooth and placement of an implant, with the intent of determining the superior treatment modality. The results demonstrated that both treatment modalities produced nearly similar success rates, with implants generally showing slightly higher success rates. It was concluded that endodontic treatment should first be given to save compromised natural tooth before pursuing extraction and implant. A protocol to assist clinicians in making the right decision to endodontically save or extract the offending tooth and replacement of implant is presented.